2004
DOI: 10.1080/02827580410017898
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of innovativeness and enterprise competitiveness in the wood products industry in finland

Abstract: Indicators of innovativeness and enterprise competitiveness in the wood products industry in Finland. Scand. J. For. Res. 19(Suppl. 5): 90 Á/96, 2004. This paper presents the results of two studies where the indicators characteristic for innovations in wood products industries were analysed and an index for the overall innovativeness was developed, and the competitiveness of the wood products enterprises was studied in relation to the indicators of innovativeness. The results of the Delphi survey (n 0/63) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 4 publications
0
27
0
2
Order By: Relevance
“…Multiple sources provide evidence that more innovative firms experience greater financial success (Rubera and Kirca, 2012;Dobni, 2010;Gibb and Haar, 2010;Han et al, 1998) and it is claimed that innovativeness is one of the most important mechanisms available to keep pace with the competition (Uzkurt et al, 2012). The positive connection between innovativeness and performance holds for forest sector firms (Nybakk, 2012;Knowles et al, 2008a;Crespell and Hansen, 2008;Välimäki et al, 2004). However, most of these studies were done during what might be called "normal" economic times when companies were not coping with the extreme turbulence of the Downturn.…”
Section: Introductionmentioning
confidence: 93%
“…Multiple sources provide evidence that more innovative firms experience greater financial success (Rubera and Kirca, 2012;Dobni, 2010;Gibb and Haar, 2010;Han et al, 1998) and it is claimed that innovativeness is one of the most important mechanisms available to keep pace with the competition (Uzkurt et al, 2012). The positive connection between innovativeness and performance holds for forest sector firms (Nybakk, 2012;Knowles et al, 2008a;Crespell and Hansen, 2008;Välimäki et al, 2004). However, most of these studies were done during what might be called "normal" economic times when companies were not coping with the extreme turbulence of the Downturn.…”
Section: Introductionmentioning
confidence: 93%
“…The core capabilities of a firm have a positive influence on the outcome of wooden products innovations (Bull and Ferguson 2005). Innovativeness has been found to have positive impacts on the competitiveness and profitability of wood products enterprises (Välimäki et al 2005). According to Korhonen (2006), creative use of information and combination of new knowledge linked to innovations are prerequisites for growth.…”
Section: Secondary Processing Firms and Wood Products Within Pulp Andmentioning
confidence: 99%
“…The results of the pre-tests led to some valuable adjustments of the questions and the structure of the questionnaire. For example, it was indicated that information required for more sophisticated indicators of innovativeness, e.g., "R&D investment'" and "share of new products from total turnover" (Välimäki et al 2004) was difficult for managers to provide. The questionnaire was Furtherprocessed goods = impregnated goods, poles, panelling, mouldings, floorings, planed construction wood, blanks for joinery or furniture industry, engineered wood products, building modules c) Spruce focus = a raw material mix consisting of more than 66% spruce; pine focus = a raw material mix consisting of more than 66% pine; hardwood focus = a raw material mix consisting of more than 66% hardwood (in subsequent analyses where data about raw material mix were used, SBUs with a hardwood focus were excluded from analysis due to the small size of this group); no focus = neither a spruce, pine nor hardwood share of more than 66%.…”
Section: Data Collectionmentioning
confidence: 99%
“…This lack of precision and consistency might be a consequence of the difficulties associated with the measurement of such a complex concept as innovativeness. After all, because "[innovativeness] is a strategic, cultural, social, and managerial issue" (Välimäki et al 2004) it leaves a lot of possibilities for different approaches in operationalization. And perhaps Rogers (1998) has a point when he states that because innovativeness is such a multifaceted and complex organizational trait, there is no single measure that can capture the concept.…”
Section: Organizational Innovativenessmentioning
confidence: 99%